Toxicology of Nuclear Polyhedrosis Virus, Botanical and Synthetic Pesticides on Mortality Rate of Crocidolomia binotalis (Zeller) - Bakhroini Habriantono; Suharto Suharto; Wagiyana Wagiyana; Mohammad Hoesain; Mochammad Wildan Jatmiko; Sigit Prastowo; Ankardiansyah Pandu Pradana; Anggi Anwar Hendra Nurdika; Fariz Kustiawan Alfarisy (مجلة بغداد للعلوم)
Crocidolomia binotalis (Cb) (Zeller) is one of the main pests of cabbage which is difficult for farmers to control in the Ijen Crater in Indonesia. The demand for cabbage in Indonesia is increasing every year, so intensification efforts are continuously being made. Farmers intensively use synthetic pesticides as the primary control of Cb. The purpose of this study is to examine several control agents that can be used as an alternative to synthetic pesticides. Then, it provides recommendations to Ijen Crater farmers to adapt in reducing the use of synthetic pesticides. The biopesticide used was based on the Nuclear Polyhedrosis Virus strains of Spodoptera litura (SlNPV) and Helicoverpa armigera (HaNPV), botanical pesticides, and synthetic pesticides as a comparison treatment. SlNPv and HaNPV isolates were obtained from the Indonesian Sweetener and Fiber Crops Research Institute. The botanical pesticide formulas come from a combination of Azadiracta indica, Aglaia odorata, Ageratum conyzoides dried for one week and proposed to form flour. Then, it was extracted using 96% ethanol solvent, 0.5% tween 90 using a rotary evaporator at a temperature of 40oC. For synthetic pesticide, the treatment used the active ingredient Permethrin 20 mgL-1. The cb collected from the field was re-filtered in a Petri dish by providing artificial feed soaked with this material for 5 minutes. The highest mortality test results were found in the botanical pesticide formula with a value of 100% at 72 hours. Mortality in SlNPV and HaNPV tended to be stable with a maximum value of 72.02%. The results of mortality testing in the laboratory can be a recommendation for alternative control of Cb pests in cabbage plants in the field. In this case, it is an effort to reduce farmers' dependence on using synthetic pesticides.